A case series on isolated maxillary sinus involvement in mucormycosis - Praveen Kumar J; Sengottuvelu P; Semmanaselvan K; Pavithra JR (Asian Journal of Medical Sciences, 2023)
Mucormycosis is a potentially fatal fungal infection that can affect various parts of the body, including the sinuses. Isolated maxillary sinus involvement usually indicates an early diagnosis of Mucormycosis. The aim of the study was to present a case series on the clinical presentation and management outcomes in patients with isolated maxillary sinus involvement in Mucormycosis to emphasize on the early diagnosis and management of the condition. A retrospective study of 10 patients who presented to the RGGGH ENT department with isolated maxillary sinus involvement in Mucormycosis that was confirmed by diagnostic nasal endoscopy, CT scan and fungal KOH swab and who were managed by endoscopic sinus surgery. In our study, out of 10 cases, two patients had unilateral symptoms and eight patients had bilateral symptoms. Most common presentation was nasal obstruction, nasal discharge, and facial pain. Complete disease clearance was achieved in all cases by endoscopic sinus surgery with debridement. Diabetes was the most common underlying comorbidity, present in all 10 patients. All patients were treated with a combination of antifungal therapy and surgical debridement. All patients showed improvement on followup, with no recurrence or mortality reported during the follow-up period. Mucormycosis with isolated maxillary sinus involvement is a timely presentation of mucormycosis but potentially life-threatening due to the nature of the disease to spread rapidly. Prompt diagnosis and management are crucial for improving outcomes in these patients. A combination of antifungal therapy and surgical debridement appears to be an effective treatment approach in these patients.